Originally Single Word Borrowing from English in My Stupid Boss: An Analysis of their Syntactical Position in Indonesian Language - Dalilan Dalilan (ELITE JOURNAL, 2023)
Borrowing words from other languages is a linguistic phenomenon. Word borrowing occurred as a result of contact between two languages or more. Words or a single word taken from a foreign language such as English can be found both in spoken and written forms of communication. English is the most important linguistic source from which its words are borrowed by Bahasa Indonesia (BI). This qualitative study aims at analyzing syntactical positions of originally single word borrowing from English. Data of the study are in the forms of originally English single word categories such as nouns, verbs, adjectives, and adverbs collected from a popular novel book entitled My Stupid Boss 3 and 4 published by Gradien Mediatama. Purposive sampling technique was used to collect data involving the selection of those data that suit the purposes of the analysis. Data were analyzed by way of explaining purposively selected data. The results indicated that single parts of speech such as noun, adjevtive, verb, and adverb existing in the construction of BI follow the syntactical rules of the language. In conclusion, the process of borrowing these originally single word categories from English is governed by syntactical rules of the language. Keywords: single word, word borrowing, syntactical position